FACTORS HINDERING THE IMPLEMENTATION OF THE MINISTER OF HOME AFFAIRS REGULATION NO. 84/2015 ON THE STRUCTURE AND WORK PROCEDURES OF THE VILLAGE GOVERNMENT IN SEREH VILLAGE, JAYAPURA REGENCY - Toroby, Renida Joselina; Wulandari, Nyariana Hadiyanti (Transpublika Publisher, 2024)
The focus of this research is to explore the barriers that hinder the enforcement of Minister of Home Affairs Regulation Number 84 of 2015 regarding the Structure and Operating Procedures of the Village Government in Sereh Village, Sentani District, Jayapura Regency. Qualitative research methodology was utilized for this study. Data was gathered through observations, interviews, documentation, and literature reviews. The data was analyzed using techniques such as data reduction, data presentation, and conclusion/validation. The findings of this study suggest that the Sereh Village Government prioritizes simplicity and efficiency in policy implementation to ensure optimal service delivery. However, in the process of implementing the regulation of the Minister of Home Affairs number 84 of 2015, communication and resources. Communication is currently restricted to activities related to developmental planning and socialization at the sub-district level. Furthermore, related to the placement of human resources, some are still not in accordance with their competencies. It is important to support and provide guidance to relevant agencies and village officials as they fulfill their responsibilities, roles, and positions in Kampung Sereh, Sentani District, Jayapura Regency, ensuring compliance with laws and regulations while considering the unique needs of the community and local traditions.